A CONCEPTUAL FRAMEWORK FOR GREEN CAREER AND TECHNICAL EDUCATION: SUSTAINABILITY AND THE DEVELOPMENT OF A GREEN-COLLAR WORKFORCE - A. Gregson, James (Journal of Technical Education and Training, 2010)
Background/Context: In this paper sustainability is explored as an emerging paradigm for career and technical education (CTE). The current context of the sustainability or green movement is discussed and CTE is compared to environmental education. A sustainability literacy conceptual framework is then applied to career and technical education. Purpose/Focus of Study: An argument is presented that CTE programs should green their curriculum and instruction to meet the needs of students, employers, business/industry and the environment. It is then argued that a sustainability literacy conceptual framework is needed to assess current efforts by CTE programs to green their curriculum and instruction, shape and inform future efforts and to assess sustainability efforts in CTE. Research Design: This paper is an analytic essay in which the historical, philosophical, and theoretical foundations of CTE are reviewed and then related to environmental education. Sustainability is defined, examined and applied through a sustainability literacy conceptual framework to CTE. Conclusion: Green CTE represents a new paradigm for the field and sustainability is a complex not yet well understood concept. This paper is intended to stimulate conversation about the purpose(s) of CTE as well as the possible role CTE has in contributing to sustainability through local actions.